Reforming civil-military relations in new democracies democratic control and military effectiveness in comparative perspectives - Croissant, Aurel; Kuehn, David (Springer, 2017)
This book addresses the challenge of reforming defense and military policy-making in newly democratized nations. The empirical and theoretical findings presented here will appeal to scholars of civil-military relations, democratization and security issues, as well as to defense policy-makers.